Teaching Phonics Through Video: Connecting Letter Sounds and Sign Language for Kinesthetic Children - Komalasari, Dewi; Sukartiningsih, Wahyu; Hendratno, H.; Suryanti, S.; Adi, Agus Satmoko (International Journal of Language Education, 2025)
This research aims to develop video learning to recognize vowel letters through sign language with an approach that is suitable for children with kinesthetic learning styles, who often experience difficulties in the traditional learning process. This research draws on multiple learning intelligences, particularly kinesthetic intelligence, which emphasizes that children learn best through physical activity. The research method follows the ADDIE model, which includes the steps of needs analysis, content design, video development, implementation, and evaluation, to ensure that the final product meets the criteria of effective learning. Based on unstructured interview data, teachers emphasized the importance of the specific features of letters. The implementation of this method was indicated to be successful, showing that 83.33% of students from groups A1 and A2 made significant progress in recognizing vowel letter sounds, with an average n-gain of 0.81 (A1) and 0.83 (A2). Although there were challenges for 20% of students in the speed of letter shape recognition and imitation, these results support the need for a diverse and inclusive approach to learning. The research recommends collaborative learning strategies for children who struggle with letter recognition and emphasizes the importance of using methods that support all learning styles. The implications of the findings lie in developing more effective learning media, encouraging active and interactive learning that strengthens children's literacy and communication skills. The originality of this research lies in the integration of Indonesian letter sounds, the use of sign language and the learning steps of kinesthetic children. This research makes the subject matter more accessible to children with kinesthetic learning styles and makes a significant contribution to modern learning methodologies